2006
DOI: 10.1007/s11083-006-9039-8
|View full text |Cite
|
Sign up to set email alerts
|

Rook Poset Equivalence of Ferrers Boards

Abstract: Abstract. A natural construction due to K. Ding yields Schubert varieties from Ferrers boards. The poset structure of the Schubert cells in these varieties is equal to the poset of maximal rook placements on the Ferrers board under the Bruhat order. We determine when two Ferrers boards have isomorphic rook posets. Equivalently, we give an exact categorization of when two Ding Schubert varieties have identical Schubert cell structures. This also produces a complete classification of isomorphism types of lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…What is true for skew Ferrers boards? • Develin [7] classified the isomorphism types of lower Bruhat intervals of 312-avoiding permutations by using the connection to rook posets discovered by Ding [8]. What are the isomorphism types of lower Bruhat intervals of permutations that avoid the patterns 4231, 35142, 42513, and 351624?…”
Section: Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is true for skew Ferrers boards? • Develin [7] classified the isomorphism types of lower Bruhat intervals of 312-avoiding permutations by using the connection to rook posets discovered by Ding [8]. What are the isomorphism types of lower Bruhat intervals of permutations that avoid the patterns 4231, 35142, 42513, and 351624?…”
Section: Open Problemsmentioning
confidence: 99%
“…Really small intervals (of length 7 in A n and 5 in B n and D n ) were completely classified by Hultman [13] and Incitti [14]. Lower intervals of 312-avoiding permutations in A n were classified by Develin [7] (though he did not compute their Poincaré polynomials), and for a general lower interval [id, w] in a crystallographic Coxeter group, Björner and Ekedahl [3] showed that the coefficients of Poin [id,w] (q) are partly increasing. Reading [20] studied the cdindex and obtained a recurrence relation for the Poincaré polynomials of the intervals in any Coxeter group [19]; however he did not compute these for any particular intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrers graphs/tableaux have a prominent place in the literature as they have been studied in relation to chromatic polynomials [2,18], Schubert varieties [16,15], hypergeometric series [29], permutation statistics [9,18], quantum mechanical operators [50], and inverse rook problems [23,16,15,42]. More generally, algebraic and combinatorial aspects of bipartite graphs have been studied in depth (see, e.g., [46,30] and the comprehensive monograph [51]).…”
Section: Introductionmentioning
confidence: 99%
“…Ferrers graphs/tableaux have a prominent place in the literature as they have been studied in relation to chromatic polynomials [4,23], Schubert varieties [21,18], hypergeometric series [33], permutation statistics [9,23], quantum mechanical operators [64], and inverse rook problems [27,21,18]. More generally, algebraic and combinatorial aspects of bipartite graphs have been studied in depth (see, e.g., [61,35,25,13,14,49,22] and the comprehensive monographs [36,66]).…”
Section: Introductionmentioning
confidence: 99%